PENGARUH MOTIVASI DAN PERSEPSI KUALITAS TERHADAP MINAT BELI LAPTOP PADA MAHASISWA TANGERANG - Satrio, Adhi; Rachmi Adiarsi, Gracia (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2019)
The development of information technology makes it easy for community members to interact with other members of society not limited to space and time. The producers create various forms of computers which are technological tools to facilitate communication. Desktops, laptops or notebooks with various brands on the market. The public is faced with offering laptop brands such as Apple, Asus, Acer, Dell, Lenovo, HP, and other brands. Based on data on global laptop shipments in 2017 there were 164.7 million units. The Apple brand outperformed Asus and won 4th place the previous year ranking 5. The success of Apple with Macbook Pro products in 2017 showed an increase in buying interest in Apple laptops. This is inseparable from Apple's laptop products perceived quality and meet what consumers want from a brand. The purpose of this study is to see whether motivation and perceived quality affect buying interest in Apple laptops and analyze the influence of motivation and perceived quality on interest in buying Apple laptops. The theory used is motivation theory, perceived quality, buying interest. The method used is a quantitative method by collecting data through a questionnaire. Based on the results of the study, it was found that motivation and perceived quality had a significant effect on buying Apple brand laptops. Motivation and perceived quality simultaneously have a significant effect on buying Apple brand laptops with students from private universities in Tangerang